Multi-Robot Remote Interaction with FS-MAS. (22nd February 2013) - Jiang, Yunliang; Zhang, Xiongtao; Tang, Liang; Liu, Weicong; Fan, Jing; Liu, Yong
The need to reduce bandwidth, improve productivity, autonomy and the scalability in multi-robot teleoperation has been recognized for a long time. In this article we propose a novel finite state machine mobile agent based on the network interaction service model, namely FS-MAS. This model consists of three finite state machines, namely the Finite State Mobile Agent (FS-Agent), which is the basic service module. The Service Content Finite State Machine (Content-FS), using the XML language to define workflow, to describe service content and service computation process. The Mobile Agent computation model Finite State Machine (MACM-FS), used to describe the service implementation. Finally, we apply this service model to the multi-robot system, the initial realization completing complex tasks in the form of multi-robot scheduling. This demonstrates that the robot has greatly improved intelligence, and provides a wide solution space for critical issues such as task division, rational and efficient use of resource and multi-robot collaboration.